Self-Image and Beauty Standards in the Drama My ID is Gangnam Beauty: Citra Diri dan Standar Kecantikan dalam Drama My ID is Gangnam Beauty - Dea Ramadhanty; Nur Maghfirah Aesthetika (Academia Open, 2023)
General Background the representation of self-image in media plays a significant role in shaping societal beauty standards. Specific Background this study focuses on the perceptions of audiences regarding self-image in the South Korean drama My ID is Gangnam Beauty, which addresses issues of beauty and self-esteem. Knowledge Gapw while existing literature examines beauty standards, there is limited research on audience reception and the impact of specific media portrayals on self-image perceptions. Aims the research aims to explore how young adults interpret the concept of self-image as presented in the drama and to identify the standards of beauty that resonate with them. Results findings indicate that over 80% of participants believe visual beauty is crucial, yet they also challenge the notion of rigid beauty standards. Audiences recognized that external perceptions do not always align with self-perception, leading to feelings of insecurity. Novelty this study provides insight into the complexity of audience reception and the dynamic nature of self-image influenced by media representations. Implications the results underscore the importance of fostering self-love as a means to cultivate authentic self-identity and challenge prevailing beauty norms, suggesting that media can be a catalyst for discussions about individual worth beyond conventional beauty standards. Highlights: Majority view visual beauty as important yet challenge rigid standards. External perceptions can differ from personal self-image. Emphasizing self-love promotes authentic self-identity. Keywords: Self-Image, Beauty Standards, Audience Perception, Drama, Insecurity